Spiritual Neuroscience Learning at Aisyiyah East of Tebet, South Jakarta - Hasnida; Masyitoh; Tumanggor, Rusmin (Asian Journal of Contemporary Education, 2019)
Spiritual neuroscience is one of neuroscience sub-discipline which specialized in a study over brain and human spiritualism. Spiritual neuroscience study is aimed to enhance early childhood’s potentials, particularly, brain spiritualism. This research is directed to answer, to know, and to analyze over a study of spiritual neuroscience in a Kindergarten called TK Aisyiah 4, East Tebet , South Jakarta. Research result showed that spiritual neuroscience indicators are the meaning of life, positive emotions, spiritual experience and ritual that have been taught to the pupils at TK Aisyiah 4, Tebet Timur, Jakarta Selatan. The advance of spiritual-neuroscience study is it will develop spiritual potential over children in the early childhood phase and stimulate them to be religious. Childhood is a period of preparation, training and habituation. A spiritually intelligent individual is not only able to solve life's problems in a rational or emotional way, but it also relates them to the meaning of life spiritually.